Study of performance of aerostat envelope materials on the coast - Lv, Jing; Zhou, Yan; Zhang, Yuanping; Nie, Ying; Wang, Qian (Frontiers in Materials, 2022)
In this paper, the performance of several envelope materials natural aged in Hainan, China, has been studied. Results show that the outer layer contributes to the properties of envelope materials, where PVF and PVDF are better candidates for weathering layer in contrast with TPU and aluminum ones. Due to better water and mildew resistance of PVF and PVDF, the loss of tensile strength for 3216LV and FV1175 was slight, whose value reduced from 101.43±5.45 Kgf/cm, 76.15±3.81 Kgf/cm to 79.73±6.40 Kgf/cm and 70.20±6.57 Kgf/cm, respectively, when aging for 24 months with the helium permeability reduction from 0.8818 L/m2•day•atm and 0.6360 L/m2•day•atm to 0.2047 L/m2•day•atm and 0.2169 L/m2•day•atm aging for 18 months, where FV1175 shower leakage when aging for 24 months due to delamination. However, the tensile strength of HV150 dropped from 82.13±3.61 Kgf/cm to 15.22±2.16 Kgf/cm at 24 months with helium leakage owing to heavily mildew and degradation. Meanwhile, ETAV150 also exhibited decreased tensile strength of 57.92±1.32 Kgf/cm after 6 months aging, which was 32.8% lower than that of original sample and showed leakage when aging for 12 months. This research provides a theoretical guidance for structure design and screen of envelope materials for aerostat used along coast.